Access to healthcare for the most vulnerable migrants: a humanitarian crisis - Pottie, Kevin; Martin, Jorge P; Cornish, Stephen; Biorklund, Linn M; Gayton, Ivan; Doerner, Frank; Schneider, Fabien (Université d'Ottawa | University of Ottawa, 2015)
Abstract A series of Médecins Sans Frontières projects for irregular migrants over the past decade have consistently documented high rates of 14 physical and sexual trauma, extortion and mental illness amidst severe healthcare, food, and housing limitations. Complex interventions were needed to begin to address illness and barriers to healthcare and to help restore dignity to the most vulnerable women, children and men. Promising interventions included mobile clinics, use of cultural mediators, coordination with migrant-friendly entities and NGOs and integrating advocacy programs and mental health care with medical services. Ongoing interventions, research and coordination are needed to address this neglected humanitarian crisis.